2021
DOI: 10.1111/jbi.14243
|View full text |Cite
|
Sign up to set email alerts
|

Do host‐associated microbes show a contrarian latitudinal diversity gradient? Insights from Mytilus californianus, an intertidal foundation host

Abstract: Aim The latitudinal diversity gradient (LDG) is one of the most pervasive large‐scale trends in biodiversity. However, whether microbial taxa also conform to this pattern remains poorly known. This study uses the gill and shell‐surface microbiomes of the marine bivalve Mytilus californianus to test whether the diversity of host‐associated microbial communities declines with increasing latitude, as predicted by the LDG. Location Northeastern Pacific coast, ranging from Sitka, AK to La Jolla, CA, USA (spanning 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 95 publications
0
9
0
Order By: Relevance
“…Studies in anemones (Morelan et al, 2019) and fruit flies (Corby‐Harris et al, 2007) spanning limited latitudinal ranges (8 and 10°, respectively) found no differences in bacterial microbiome diversity. In contrast, geographical patterns were found in the California blue mussel across a latitudinal range of 24° (Neu et al, 2021). However, results depended on the tissue type, diversity metric and taxonomic scale, and they varied across bacterial clades (Neu et al, 2021).…”
Section: Open Eco‐evolutionary Questions In Microbiome Researchmentioning
confidence: 97%
See 3 more Smart Citations
“…Studies in anemones (Morelan et al, 2019) and fruit flies (Corby‐Harris et al, 2007) spanning limited latitudinal ranges (8 and 10°, respectively) found no differences in bacterial microbiome diversity. In contrast, geographical patterns were found in the California blue mussel across a latitudinal range of 24° (Neu et al, 2021). However, results depended on the tissue type, diversity metric and taxonomic scale, and they varied across bacterial clades (Neu et al, 2021).…”
Section: Open Eco‐evolutionary Questions In Microbiome Researchmentioning
confidence: 97%
“…Microbiome diversity could also be structured differently across varying spatial scales, ranging from a few kilometres across elevations to potentially thousands of kilometres across latitudes. Latitudinal diversity gradients of bacterial microbiomes are commonly investigated across hundreds to thousands of kilometres, but ranges vary substantially among studies (e.g., between 8 and 24 degrees of latitude in the studies by Morelan et al, 2019; Neu et al, 2021), and variation across such studies could be leveraged to test whether geographical scale affects the likelihood of observing biogeographical microbiome patterns. Dispersal rates also vary considerably across host species, raising the question of whether stronger microbiome structuring along environmental gradients might be expected for hosts with lower dispersal.…”
Section: General Considerations For Studying the Geographical Distrib...mentioning
confidence: 99%
See 2 more Smart Citations
“…performed at different scales, are inconsistent (Tedersoo et al, 2014;Neu et al, 2021). Even under the same environmental conditions can the distribution of soil microorganisms be inconsistent (Han et al, 2015;Li et al, 2019;Tian et al, 2022).…”
mentioning
confidence: 99%